Cross-Education Related to the Ipsilateral Limb Activity on Monopedal Postural Control of the Contralateral Limb: A Review - Paillard, Thierry (Frontiers in Physiology, 2020)
Cross-education is the effect whereby the ipsilateral limb training generates contralateral effects as part of motor tasks requiring strength and skills. However, it is not yet known if cross-education applies to postural control which could be essential as part of human motricity. Hence, this review addresses the possible effects of acute and chronic unilateral exercises (i.e., fatiguing exercises and regularly repeated /training exercises, respectively) on the contralateral monopedal postural control. Evidence suggests that fatiguing exercises disturb the contralateral monopedal postural control. This disturbance emanates from spinal and supra-spinal alterations which provokes changes to the motor function of the contralateral limb and degrades its postural control. Unilateral training produces cross-education related to postural control, especially when it includes balance exercises, but this remains to be tested when it includes resistance exercises. Mechanistic explanations are proposed to explain how neurophysiological changes operate in the disturbance or improvement of the contralateral monopedal postural control after unilateral fatiguing exercises or training exercises (respectively) of the lower-limb.